2015
DOI: 10.1007/s00256-015-2290-6
|View full text |Cite
|
Sign up to set email alerts
|

Cone-Beam CT in diagnosis of scaphoid fractures

Abstract: CBCT is a superior alternative to radiography, entailing more accurate diagnoses of carpal region fractures, and thereby requiring fewer follow-up MRI examinations. However, CBCT cannot be used to exclude scaphoid fractures, since MRI identified additional occult scaphoid fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 27 publications
1
31
1
Order By: Relevance
“…Our findings are consistent with a recent study by Edlund et al [28], who found that CBCT was a reliable examination for the diagnosis of scaphoid fracture. However, in their study, not every patient underwent both types of imaging exams (CBCT and MRI), and in the MRI was carried out 15 days after the CBCT.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are consistent with a recent study by Edlund et al [28], who found that CBCT was a reliable examination for the diagnosis of scaphoid fracture. However, in their study, not every patient underwent both types of imaging exams (CBCT and MRI), and in the MRI was carried out 15 days after the CBCT.…”
Section: Discussionsupporting
confidence: 94%
“…The additional fractures mainly included a higher number of (avulsion) fractures of the proximal carpal row, with a higher accuracy for carpal injury than previously published [ 12 ]. Recent studies have described this pattern of additional diagnoses also for cone beam CT [ 17 ] and even for sonography [ 18 ]. However, in contrast to most of these studies on selected patient groups, this was the first study that prospectively investigated CT as an imaging tool in all patients with clinical suspicion of wrist fractures, with a multiobserver study on treatment impact.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT has excellent sensitivity for the detection of small bone and joint trauma. MRI remains the gold standard for the evaluation of occult fractures, 77 but accessibility and potential contraindications mean that CBCT can play an important role in the evaluation of patients with suspected fractures and normal radiographs, in particular in sites with overlapping bony structures such as the wrist or foot and can remove the need for MRI at a later date 77 (►Fig. 7).…”
Section: Cone Beam Ctmentioning
confidence: 99%